The prevalence of trauma from occlusion as the aggravating factors of periodontitis - Sunnati ,; Zulfan M ALIBASYAH; Sri Rezeki; Nurul Mustabsyirah Rafi'i (Dentistry Faculty, 2020)
Trauma from occlusion (TFO) is a local factor that can exacerbate tissue inflammation in periodontitis cases. There have been many clinical studies on TFO, but the prevalence of patients is currently unknown. The purpose of this study was to determine the majority of TFO cases as a factor that aggravates periodontitis based on the medic records at Oral and Dental Hospital, Universitas Syiah Kuala, Banda Aceh, Indonesia in 2017-2019. This study used a comprehensive sampling approach to evaluate 10,532 medical records associated with periodontal disease, including factors such as age, sex, causes, and TFO treatment. Descriptive data analysis showed that from a total of 10,532 medical records, there were 391 medical records related to periodontia. A total of 194 samples matched the inclusion criteria. There were 79 TFO patients (40.7%), 3 TFO cases (1.5%), and 112 cases (57.7%) other periodontal diseases without TFO. The prevalence of TFO as a dominant factor aggravating chronic periodontitis at the Oral and Dental Hospital, Syiah Kuala University, Banda Aceh Indonesia in 2017-2019. Patients with elderly age and female sex predominantly experience periodontitis which is aggravated by TFO.KEYWORDS: Occlusal adjustment blocking method, periodontitis, Trauma from occlusion